2016
DOI: 10.1111/acer.13066
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Fetal Alcohol Spectrum Disorders

Abstract: Background The term Fetal Alcohol Spectrum Disorders (FASD) defines the full range of ethanol-induced birth defects. Numerous variables influence the phenotypic outcomes of embryonic ethanol exposure. Among these variables, genetics appears to play an important role yet our understanding of the genetic predisposition to FASD is still in its infancy. Methods We review the current literature that relates to the genetics of FASD susceptibility and gene-ethanol interactions. Where possible, we comment on potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 137 publications
1
95
0
Order By: Relevance
“…Only a handful of gene-ethanol interactions have been identified to date. A detailed discussion of these interactions can be found elsewhere, 87,88 whereas here, we focus on findings in zebrafish. The many genetic tools available in zebrafish have proven successful in expanding our understanding of developmental biology.…”
Section: Identifying Gene-ethanol Interactions: the Way Of The Fishmentioning
confidence: 99%
“…Only a handful of gene-ethanol interactions have been identified to date. A detailed discussion of these interactions can be found elsewhere, 87,88 whereas here, we focus on findings in zebrafish. The many genetic tools available in zebrafish have proven successful in expanding our understanding of developmental biology.…”
Section: Identifying Gene-ethanol Interactions: the Way Of The Fishmentioning
confidence: 99%
“…Many of the hallmark phenotypes of FASD are also produced with disruption of gene function in zebrafish (Eberhart et al, 2016). Relevant to these studies, our previous work showed agrin morphants displayed similar ocular defects to those induced by ethanol exposure, suggesting agrin as a target of prenatal ethanol exposure (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Among the proposed models in this group are: alteration of the normal DNA methylation pattern and other epigenetic changes at the level of chromatin modifications, aberrant cell death (apoptosis), changes in growth and signaling factor expression (including IGF, EGF, and Shh), changes in cell adhesion, cytoskeleton and migration, abnormal inflammatory responses, changes in cholesterol homeostasis, deficient neurotransmitter signaling (choline), and changes in miRNA expression. The different models to explain FASD have been reviewed in a number of instances over the years (Caputo, Wood, & Jabbour, ; Chater‐Diehl, Laufer, & Singh, ; Eberhart & Parnell, ; Ehrhart et al, ; Gilbert‐Barness, ; Gupta, Gupta, & Shirasaka, ; Kalisch‐Smith & Moritz, ; Kane & Drew, ; Lunde et al, ; Lussier, Weinberg, & Kobor, ; Mandal, Halder, Jung, & Chai, ; Shabtai & Fainsod, ; Shenoda, ; Wells, Bhatia, Drake, & Miller‐Pinsler, ). In this review, we will focus on the reduction of retinoic acid signaling by alcohol exposure during early development and briefly summarize a few of the other related changes.…”
Section: The Etiology Of Fasdmentioning
confidence: 99%